Impoliteness Impoliteness Strategies in Amy Poehler’s Moxie (2021): A Pragmatic Analysis - Milfandia Hasan; Suleman Bouti; Indri Wirahmi Bay (Transbahasa, 2026)
This study aims to identify the types of impoliteness strategies and determine the most dominant strategy employed by the characters in the movie Moxie (2021). Utilizing a qualitative descriptive method, this research applied Jonathan Culpeper’s (1996) impoliteness theory to systematically analyze the cinematic dialogues. Data were collected through movie observation, note-taking, and transcription. The findings reveal a total of 31 instances of impoliteness, comprising five strategies: bald on record (9 data), positive impoliteness (15 data), negative impoliteness (4 data), sarcasm or mock politeness (2 data), and withhold politeness (1 datum). Positive impoliteness emerged as the most dominant strategy. The frequent use of positive impoliteness indicates that characters primarily attack the interlocutors' social identity and need for approval, utilizing relational aggression and social exclusion. In conclusion, impoliteness in Moxie functions beyond mere offensive language; it acts as a strategic communicative tool for characters to negotiate power, construct social hierarchies, and express resistance within a complex adolescent environment.